1992
DOI: 10.1042/cs0830199
|View full text |Cite
|
Sign up to set email alerts
|

Raised resting energy expenditure in Parkinson's disease and its relationship to muscle rigidity

Abstract: 1. Resting energy expenditure was measured, by indirect calorimetry, in 12 patients with Parkinson's disease and in eight healthy age-matched control subjects. In the patients with Parkinson's disease measurements were made in both the untreated state and after an injection of the dopamine agonist apomorphine (treated state). In each state muscle rigidity was recorded. 2. Resting energy expenditure was higher in patients with Parkinson's disease in both the treated and untreated states than in the control subj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
81
0
2

Year Published

2003
2003
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(89 citation statements)
references
References 3 publications
6
81
0
2
Order By: Relevance
“…Such mitochondrial derangements would cause excessive heat production, accounting for the appearance of hypermetabolism, while potentially causing an energy defi cit, leading to cellular degradation [31] . If this pathophysiological mechanism has also been suspected in other neurodegenerative diseases such as Alzheimer's disease, Parkinson's disease, as well as in tissue injury from strokes hypermetabolism was not necessarily found in these diseases [25,26,[32][33][34] . In fact, it could be interesting to defi ne what the possible metabolic mitochondrial derangements are within the subpopulation of hypermetabolic patients.…”
Section: Discussionmentioning
confidence: 99%
“…Such mitochondrial derangements would cause excessive heat production, accounting for the appearance of hypermetabolism, while potentially causing an energy defi cit, leading to cellular degradation [31] . If this pathophysiological mechanism has also been suspected in other neurodegenerative diseases such as Alzheimer's disease, Parkinson's disease, as well as in tissue injury from strokes hypermetabolism was not necessarily found in these diseases [25,26,[32][33][34] . In fact, it could be interesting to defi ne what the possible metabolic mitochondrial derangements are within the subpopulation of hypermetabolic patients.…”
Section: Discussionmentioning
confidence: 99%
“…PD patients exhibit lower body weight in comparison to age-matched subjects (Chen et al, 2003). The cause is unknown, and various mechanisms of reduced food intake (Kunig et al, 2000;Muller et al, 2001; reduced intestinal motility (McDonald et al, 2003) or increased energy expenditure due to increased involuntary movements (Markus et al, 1992) are proposed. Limited feeding experiments in our laboratory reveal no difference in food intake between ak and wt mice (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Depression, which develops either as a reaction to the diagnosis of a chronic and progressive disease, or as a result of neurotransmitter deficiency in 25 -30% of patients (Richard et al, 1997), is often associated with reduced food intake. Furthermore, it has been suggested that the disease promotes underweightness by increasing basal metabolism, but the results of metabolic studies have not been univocal: basal metabolism measured by indirect calorimetry was increased in three studies (Levi et al, 1990;Broussolle et al, 1991;Markus et al, 1992), but not in a fourth (Toth et al, 1997), which actually found a reduction in daily energy consumption in PD patients as compared to healthy controls using the technique based on double labeled water ( 2 H 2 , 18 O). What is more, the majority of PD patients are elderly and physiological aging is associated with functional losses that promote undernutrition, such as the reduction in digestive secretions, in intestinal absorption and in protein synthesis and with other factors that reduce dietary intake, such as impairment of the senses of smell and taste, and of mastication due to loss of teeth and poorly functioning dental prostheses (Jensen et al, 2001).…”
Section: Introductionmentioning
confidence: 99%